Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Vasiliki Lagou (Nature Portfolio, 2021)
Sex differences in fasting glucose and insulin have been identified, but the genetic loci underlying these differences have not. Here, the authors perform a meta-analysis of genome-wide association studies to detect sex-specific and sex-dimorphic loci associated with fasting glucose and insulin.